Dissent and the Dynamics of Cultural Change Lessons from the Underground Presses of the Late Sixties. - Pifer, Matthew T. (Milton : Routledge, 2019)
Dissent and the Dynamics of Cultural Change: Lessons from the Underground Presses of the Late Sixties, examines alternative presses' critique of culture at a time of infamous transformation and revolution in the United States. In this new study, author Matthew Pifer seeks to delineate the structure of dissent to better understand how cultural change is realized, and explores the relationships between the public and those cultural institutions that define the values and social norms that shaped daily life.
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Underground press publications -- United States -- History -- 20th century; Nineteen sixties; LITERARY CRITICISM / Books & Reading